A BODIPY-based probe for amyloid-β imaging in vivo. Issue 8 (16th March 2023) - Zhu, Mingguang; Zhang, Guoyang; Hu, Ziwei; Zhu, Chaofeng; Chen, Yixiang; James, Tony D.; Ma, Lijun; Wang, Zhuo
Abstract : Probe BocBDP with a binding unit suitable for penetrating the BBB and imaging Aβ in vivo . Abstract : Alzheimer's disease (AD) is a neurodegenerative disease, and the efficient detection of amyloid-β (Aβ) plaques can greatly enhance diagnosis and therapy. Most reported probes used to detect Aβ are based on the N, N -dimethylamino group. As such, the design of new Aβ-recognition units facilitates the recognition of Aβ. Herein, we present an Aβ recognition unit [4-(Boc-amino) benzene] used to develop BocBDP. BocBDP can recognize and image Aβ plaques both in vitro and in vivo through the interaction with amino acid residues Lys16 (K16), Val18 (V18), and Glu22 (E22). The hydrogen bonding interaction (1.9 Å) between the carbonyl oxygen atom in the Boc unit and the amino acid residue K16 allows BocBDP to bind strongly to Aβ, resulting in a five-fold fluorescence enhancement and a high affinity ( K d = 67.8 ± 3.18 nM). BocBDP can cross the BBB and image Aβ for at least 2 hours. We anticipate that our Aβ recognition unit will help improve the design of probes that specifically recognize Aβ.